Recent Developments in Modeling and Applications in Statistics - Oliveira, Paulo Eduardo (Studies in Theoretical and Applied Statistics, 2013)
Sampling and Modeling -- Estimation -- Extremes -- Testing Statistical Hypothesis -- Models with Stochastic Differential Equations -- Stochastic Processes. .